Bugis Migration to Labuhan Lombok: Social-Economic Adaptation and Maritime Transformation - Lukmanul Hakim; Lalu Murdi; Syahrul Amar; Muhammad Shulhan Hadi (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
This article examines Bugis migration to Labuhan Lombok and explains how migrant families built durable social, economic, and maritime lives in a Sasak coastal environment. The article is developed from a qualitative historical study using oral testimony, observation, documents, and relevant literature. Four stages of historical method were applied: heuristics, source criticism, interpretation, and historiography. The thesis records fourteen informants from Bugis and Sasak settlements in Labuhan Lombok. The findings identify two principal migration contexts: trade-oriented mobility associated with nineteenth-century inter-island commerce and family displacement connected to insecurity in South Sulawesi during the 1950s. Settlement was sustained through kinship chains, proximity to the sea, common Islamic affiliation, everyday exchange, interethnic marriage, and respect for local norms. Economic adaptation relied on fishing, diving, fish and shrimp-paste trading, and inter-island commerce. Maritime practices also changed from wind-powered sailing and experiential navigation to motorized boats, global positioning systems, generators, and more commercialized fish marketing. The Bugis presence in Labuhan Lombok should therefore be understood not merely as population movement, but as a locally negotiated maritime adaptation in which inherited knowledge, migrant networks, and technological change combined to produce interethnic integration and coastal economic transformation.